Advocacy of Planned Murder from the Perspective of Positive Law and Islamic Criminal Law: Comparative Study of Old and New Criminal Code Based on Decision No. 413/PID.B/2013/PN.RHL - Caesaria Okta Wahyudiana; K Kuswardani (Universitas Muhammadiyah Surakarta, 2024)
This study aims to examine how to encourage or persuade in the crime of premeditated murder in Decision No. 413/PID.B/2013/PN.RHL. The Criminal Code is something that can provide law enforcement to the community, which has now been formulated in the revision of the new Criminal Code, namely in Law No. 1 of 2023. This is the location of novelty in this research, where there is a comparison between the old Criminal Code and the new Criminal Code based on the relevant articles. The research method used is a normative method based on secondary data and literature data. The results of this study reveal that in the crime of premeditated murder based on Decision No. 413/PID.B/2013/PN.RHL the defendant is someone who persuades to carry out the crime of premeditated murder against the victim. In positive law to impose a verdict on the defendant, the panel of judges has considered according to juridical and non-juridical reviews. So that the application of the criminal sentence against the defendant is in accordance with Article 340 jo Article 55 paragraph 1 to 2 of the Criminal Code. Based on the perspective of Islamic criminal law, premeditated murder is punishable by qisash and diyat. The perpetrator of the murder could have avoided the two penalties if the victim's family accepted the forgiveness of the perpetrator without filing any charges.